PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP STRUKTUR MODAL SUBSEKTOR F&B BEI 2020-2024 - huwaidazalfa (Jurnal Ilmu Akuntansi, 2026)
The purpose of this study is to examine the effect of Profitability and Liquidity on Capital Structure in the Food and Beverage subsector listed on the Indonesia Stock Exchange during the 2020-2024 period. The research method used in this study is a quantitative method with a descriptive and verificative approach. The sampling technique used is Purposive Sampling, and data analysis is carried out using panel data regression with the Econometric Views-13 (Eviews-13) software. The results of this study indicate that Profitability affects Capital Structure, Liquidity also affects Capital Structure, and Profitability and Liquidity simultaneously affect Capital Structure. This indicates that a company's ability to generate profits and meet short-term obligations is a crucial factor in determining the company's financing policy. This study concludes that profitability and liquidity have a significant impact on capital structure, both individually and together. This shows that a company's ability to make profits and meet short-term obligations plays an important role in deciding on financing decisions. Therefore, companies are expected to manage profitability and liquidity effectively to achieve an efficient capital structure.